The Legal Practice of Corporate Takeover and Mandatory Tender Offer (MTO) in the Indonesian Capital Market - Makes, Yozua (UI Scholars Hub, 2014)
The number of takeover transactions is relatively less compared to other corporate actions by publicly-listed companies, (e.g. IPOs, rights issues, or material transactions). There is no research that explains or contextualizes this fact, but one may speculate that this may be due to (a) the existence of block-holders in Indonesia’s corporate structure profile (structural barrier) or (b) because it is costly to carry out a takeover in light of the existing Mandatory Tender Offer (MTO) requirements (legal barrier). This article focuses on the latter problem, aiming to address the practical and legal issues pertaining to takeover transactions in Indonesia with respect to the existence of the MTO. Pursuant to the prevailing rule, in a takeover of publicly-listed companies that results in a change of control, a MTO/mandatory bid requirement must be followed with the potential acquirer making an offer to purchase all of the remaining shares of the target company according to a certain minimum price formula. Specifically the article discusses practical and creative strategies that prospective controllers employ to avoid the mandatory bid/MTO requirement, and how these strategies impact the principle of minority shareholders’ protection.